Effect of Galla Chinensis on Growth and Metabolism of Microcosm Biofilms - Cheng, L.; Exterkate, R.A.M.; Zhou, X.; Li, J.; ten Cate, J.M. (Caries research, 2011)
Galla chinensis extract (GCE) interferes with de- and remineralization of dental enamel and the growth and metabolism in planktonic bacteria. However, no information is available on GCE effects on biofilms formed with saliva as inoculum. The aim of the current experiments was to investigate the effects of GCE at different stages of salivary microcosm biofilm formation. Biofilms formed on glass or enamel surfaces were treated with GCE solutions at different concentrations and at different time points. Effects were assessed by lactic acid formation and colony-forming unit (CFU) counts of the biofilms. The results showed that GCE treatments inhibited growth and acid metabolism of both nascent and mature microcosm biofilms. Pretreatment of the substratum with GCE solutions inhibited growth and lactic acid production of biofilms grown on enamel, but had little effects on biofilms formed on glass surfaces. A maximum GCE effect was found when biofilms, on either surface type, were treated after 8 h of formation with 40 h of subsequent growth. In medium with sucrose-fermenting biofilms, low concentrations of GCE (0.2 and 0.1 mg/ml) inhibited acid production without killing bacteria of the biofilm. Differences were found in GCE effects on biofilms formed with saliva from different donors, with reductions in acid formation and CFU values ranging between 0 and 78%. In conclusion, bioactive components in GCE reduce or inhibit both growth and lactic acid formation in biofilms.